Optimization of regional long-term development plans (RPJPD): a scenario planning approach - Lestari Eko Wahyudi; Laily Akbariah; Durratun Nashihah (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2025)
The implementation of scenario planning approaches provides essential tools for local governments and stakeholders to manage uncertainty and risk, ensuring that development decisions are based on relevant and accurate information. This study aims to optimize the Regional Long-Term Development Plan (RPJPD) through a scenario planning approach. This approach allows for the formulation of multiple alternative scenarios that encompass various future conditions and the evaluation of their impacts on development goals. The study employs quantitative analysis with secondary data from the RPJPD of districts/cities in East Java Province. The findings indicated that although the RPJP and RPJPD documents are flexible and can change according to conditions, they still possess significant potential to enhance local planning capacity. This condition reflects variations in performance achievement among districts/cities in East Java, with Probolinggo Regency and Probolinggo City demonstrating the best performance, while Gresik Regency and Sampang Regency ranked the lowest. Time-series analysis revealed that performance achievements on several indicators remain low, particularly regarding access to improving quality of life. This study underscores the importance of continuous evaluation and adjustment of development plans to achieve desired outcomes. It is hoped that this study will contribute significantly to improving the quality of regional development planning documents and assist local governments in achieving established development goals.